Living Hadis in the Tradition of Santri Veneration toward the Kiai: A Study of Mushafahah, Taqbil Al-Yad, and Inhina’ Practices at Pesantren Sains Tebuireng - Muhammad Fathurrohman; Mohamad Anang Firdaus; Viki Junianto (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
Pesantren, as the oldest Islamic educational institution in Indonesia, possesses various distinctive veneration traditions, among them mushafahah (handshaking), taqbil al-yad (hand-kissing), and inhinā' (bowing of the head) toward the kiai. These traditions have frequently been the subject of scholarly debate regarding their jurisprudential foundations, necessitating examination through the living hadis approach. This study aims to describe the practices of mushafahah, taqbil al-yad, and inhinā' at Pesantren Sains Tebuireng, to analyze the meanings and motivations underlying them, and to examine their correlation with the prophetic traditions of the Prophet Muhammad SAW. The study employs a descriptive qualitative approach, with data collection techniques comprising semi-structured interviews with seven informants selected through purposive sampling, field observation, documentation, and a questionnaire administered to 50 santri as supplementary data. The findings indicate that all three practices have become institutionalized as a robust collective culture within the pesantren environment. The motivations of the santri in performing these practices encompass moral character development, veneration of knowledge, cultivation of tawadhu' (humility), as well as the influence of the social environment and family education. Normatively, mushafahah possesses a strong foundation in Shahih al-Bukhari; taqbil al-yad is permissible insofar as it is intended as ta'ẓīm dīnī (religious veneration) based on the position of the majority of scholars; whereas inhinā' in the form of a slight inclination of the head does not fall within the prohibited category, taking into account the physical degree of the movement and the intention of the practitioner. From the perspective of living hadis, these traditions are more predominant in their praxis-conformative dimension than in their cognitive-textual dimension, reflecting that the transmission of values within the pesantren takes place through exemplification, habituation, and the internalization of adab